2020
DOI: 10.2196/17945
|View full text |Cite
|
Sign up to set email alerts
|

Physiological State and Learning Ability of Students in Normal and Virtual Reality Conditions: Complexity-Based Analysis

Abstract: Background Education and learning are the most important goals of all universities. For this purpose, lecturers use various tools to grab the attention of students and improve their learning ability. Virtual reality refers to the subjective sensory experience of being immersed in a computer-mediated world, and has recently been implemented in learning environments. Objective The aim of this study was to analyze the effect of a virtual reality condition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Although the fractal theory has been widely applied in the analysis of the complexity of EEG signals in different conditions [e.g., external stimulation (Babini et al, 2020), detection of brain disorders (Namazi et al, 2020)], however, based on our search, only one reported work analyzed EEG signals during locomotion using fractal theory. In (Mujib Kamal et al, 2020), we showed that the variations of the complexity of EEG signals and walking paths are correlated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fractal theory has been widely applied in the analysis of the complexity of EEG signals in different conditions [e.g., external stimulation (Babini et al, 2020), detection of brain disorders (Namazi et al, 2020)], however, based on our search, only one reported work analyzed EEG signals during locomotion using fractal theory. In (Mujib Kamal et al, 2020), we showed that the variations of the complexity of EEG signals and walking paths are correlated.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, while the larger body of literature has focused on cognitive and procedural domains, there is still a dearth of literature relating to outcomes having to do with emotion, or forms of behavioral learning. I-VR seems a promising area for behavioral and affective change, and I-VR research would greatly advance if the training research community explored learning in these non-technical, but still very important, forms of learning (Song & Fiore, 2017;Bian et al, 2015). We recommend that I-VR research work towards a more inter-professional approach.…”
Section: Integrating Findingsmentioning
confidence: 99%
“…This involves collecting the data in the virtual environment through the telemetry provided via the VR controllers and HMD (e.g., pose, posture, rate of VE interaction). New analytic techniques, such as fractal analysis to examine fractal scaling, may provide information with regard to the health of the user in the system (e.g., discomfort), and possibly the user's state of learning (Arcioni et al, 2019;Babini et al, 2020). Overall, though, we recommend that the training research community consider how it is that I-VR can more sophisticatedly assess learning.…”
Section: Integrating Findingsmentioning
confidence: 99%
“…Hoskins showed that students with strong learning abilities also performed better in online tests [27]. Babini pointed out that a virtual reality environment played a greater role in improving students' learning ability [28]. Cheng showed that high-order cognitive learning skills are positively correlated with participants' performance [29].…”
Section: Hypothesis Proposalmentioning
confidence: 99%